Modeling the rheological behavior of thermosonic extracted guava, pomelo, and soursop juice concentrates at different concentration and temperature using a new combination model - Abdullah, Norazlin; Nyuk, L. Chin; Yusof, Yus A.; A. Talib, Rosnita (Institute of Food Science & Technology, 2018)
This study has modeled the rheological behavior of thermosonic extracted pink-fleshed guava, pink-fleshed pomelo, and soursop juice concentrates at different concentrations and temperatures. The effects of concentration on consistency coefficient (K) and flow behavior index (n) of the fruit juice concentrates was modeled using a master curve which utilized the concentrationtemperature shifting to allow a general prediction of rheological behaviors covering a wide concentration. For modeling the effects of temperature on K and n, the integration of two functions from the Arrhenius and logistic sigmoidal growth equations has provided a new model which gave better description of the properties. It also alleviated the problems of negative region when using the Arrhenius model alone. The fitted regression using this new model has improved coefficient of determination, R2 values above 0.9792 as compared to using the Arrhenius and logistic sigmoidal models alone, which presented minimum R2 of 0.6243 and 0.9440, respectively.